High-stability sodium titanate negative electrode material and preparation method and application thereof

CN120637459BActive Publication Date: 2026-10-16BENAN ENERGY TECH JIANGSU CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510860439.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-25
Publication Date
2026-10-16
Estimated Expiration
2045-06-25

AI Technical Summary

Technical Problem

如专利CN115472791A公开了一种介孔钛酸钠/碳复合电极材料及其制备方法与应用,以表面活性剂为模板,得到复合电极材料,然而,该方法仍存在如何进一步提高电化学性能的问题

Benefits of technology

[0025] In this invention, a C layer, an Al2O3 layer, and a NaAlO2 layer are sequentially coated on the surface of Na2Ti3O7 material. The outer NaAlO2 layer serves as a protective layer and also provides ion channels as an ion conductor. The middle mesoporous Al2O3 layer blocks electrode liquid corrosion, and the inner carbon layer increases the material's conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120637459B_ABST
    Figure CN120637459B_ABST
Patent Text Reader

Abstract

The application discloses a kind of high stability sodium titanate negative materials and its preparation method and application, including the following steps: Na2Ti3O7@C is immersed in gamma-Al2O3 suspension, and mixed liquor is obtained, after stirring, centrifugal low-temperature sintering, and Na2Ti3O7@C-Al2O3 is obtained;Na2Ti3O7@C-Al2O3 is immersed in NaOH solution, and Al2O3 surface layer is converted into NaAlO2 by hydrothermal treatment, and Na2Ti3O7@C-Al2O3 / NaAlO2 is obtained.The application sequentially coats C layer, Al2O3 layer and NaAlO2 layer on the surface of Na2Ti3O7 material, as a protective layer, also as ion conductor to provide ion channel to increase material conductivity;Hydrothermal reaction in situ conversion generates NaAlO2 layer, interface is closely combined, avoids electrode liquid penetration, and has good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of anode material technology, specifically to a highly stable sodium titanate anode material, its preparation method, and its application. Background Technology

[0002] Sodium-ion batteries have attracted much attention as a preferred type for large-scale energy storage and smart grid applications due to their abundant resources and low cost. However, despite the many advantages of sodium-ion batteries, their practical application still faces challenges such as energy density, power density, and long-term cycle stability. The negative electrode material plays a crucial role in the battery's energy density and stability. An ideal negative electrode material should have a low discharge voltage, high theoretical capacity, and also possess good first-cycle coulombic efficiency, power characteristics, and cycle stability.

[0003] Titanium-based anode materials have attracted extensive research due to their high sodium storage activity, high stability, low cost, and non-toxicity. Among them, sodium titanate (Na₂Ti₃O₇, NTO), as a layered compound, has a high theoretical capacity and a low discharge voltage plateau (approximately 0.3V vs Na / Na). + The presence of sodium ions in the Na2Ti3O7 lattice is beneficial for improving the operating voltage and energy density of the full cell. However, the large band gap (3.7 eV) of Na2Ti3O7 material itself leads to slow sodium ion insertion / extraction kinetics. In addition, the large number of sodium insertions in the Na2Ti3O7 lattice causes severe structural strain, exposing more reactive surface sites, leading to continuous decomposition of the electrolyte and resulting in a low first-cycle coulombic efficiency, thus exhibiting poor cycling stability.

[0004] To address the aforementioned technical challenges, researchers primarily employ methods such as designing nanoparticle structures and surface doping to improve the performance of Na₂Ti₃O₇. For example, patent CN115472791A discloses a mesoporous sodium titanate / carbon composite electrode material and its preparation method and application, using a surfactant as a template to obtain the composite electrode material. However, this method still faces the challenge of further improving its electrochemical performance. Patent CN118529769A discloses a method for preparing a nanosheet-like carbon-coated sodium titanate composite material. This method obtains nanosheet-like Na₂Ti₃O₇ through modification treatment, improving the material's stability. However, this method still faces the challenge of further improving the purity and yield of the product.

[0005] In summary, existing methods for preparing titanium-based anode materials often suffer from drawbacks such as complex processes, high costs, difficulty in large-scale production, and insufficient electrochemical performance of the products. Therefore, researching and developing a simple and efficient preparation method, and improving its sodium storage performance and cycle stability through optimized material structure design, has become an important direction in current research on sodium-ion battery anode materials. Summary of the Invention

[0006] This invention addresses the shortcomings of existing technologies by providing a highly stable sodium titanate anode material, its preparation method, and its applications. A C layer, an Al2O3 (alumina) layer, and a NaAlO2 (sodium aluminate) layer are sequentially coated onto the surface of a Na2Ti3O7 material. The outer sodium ion conductor provides ion channels, the middle mesoporous Al2O3 layer blocks electrode liquid corrosion, and the inner carbon layer increases the material's conductivity. The one-step coating method using an organic sodium source avoids complex processes such as template methods and sol-gel methods. The in-situ chemical conversion of the NaAlO2 layer via hydrothermal method offers significant advantages in interfacial bonding strength, ion transport efficiency, and process compatibility.

[0007] To address the aforementioned technical problems, this invention provides a method for preparing a highly stable sodium titanate anode material, comprising the following steps:

[0008] S1. The Na2Ti3O7@C composite material was impregnated in γ-Al2O3 suspension to obtain a mixed solution. After stirring and centrifugation, it was sintered at low temperature to form an Al2O3 layer on the surface of the Na2Ti3O7@C composite material, thus obtaining the Na2Ti3O7@C-Al2O3 composite material.

[0009] S2. The Na2Ti3O7@C-Al2O3 composite material was immersed in NaOH solution, and hydrothermal treatment was performed to convert the surface layer of Al2O3 into NaAlO2, thus obtaining the highly stable sodium titanate anode material Na2Ti3O7@C-Al2O3 / NaAlO2.

[0010] This invention reduces the decomposition rate of the electrolyte through an Al2O3 / NaAlO2 bilayer coating. The mesoporous Al2O3 layer blocks electrode corrosion, while NaAlO2, containing sodium ions, acts as a protective layer and enhances the ionic conductivity of the negative electrode material. The NaAlO2 layer promotes the absorption of sodium ions. + migrate.

[0011] This invention utilizes sodium hydroxide (NaOH) hydrothermal treatment to generate an outer NaAlO2 layer on the surface of an Al2O3 layer in situ. Compared with the process of directly applying NaAlO2 to the surface of alumina through physical / chemical coating, this invention has the following technical advantages: (1) The hydrothermal reaction allows the Al2O3 surface to react with OH... -Chemical bonding occurs, and a dense and uniform NaAlO2 layer (thickness controllable to the nanometer scale) is generated in situ. The NaAlO2 coating layer and the inner Al2O3 layer are seamlessly combined, avoiding interfacial corrosion caused by electrolyte penetration; (2) The generated NaAlO2 has a continuous crystal structure, its sodium ion diffusion channels are complete, the sodium ion transport path is unobstructed, and the electrode polarization is low; (3) Low temperature hydrothermal conditions (70-90℃) avoid thermal damage to the substrate material (such as carbon coating layer or sodium titanate core) caused by high temperature; at the same time, the process temperature is low, and the energy consumption is reduced by 40%-60%; the target product is generated in one step without subsequent sintering, and the process flow is shortened by about 30%.

[0012] Furthermore, the preparation method of the Na2Ti3O7@C composite material is as follows: titanium dioxide, an organic sodium source, and water are mixed and sintered under a protective atmosphere. The organic sodium source decomposes to generate a carbon layer that coats sodium titanate particles, forming the Na2Ti3O7@C composite material. This one-step coating method using the organic sodium source avoids complex processes such as template methods and sol-gel methods, obtaining a nanoscale carbon material coating layer and solving the problem of low loading in electrode fabrication processes.

[0013] Furthermore, the titanium dioxide is anatase titanium dioxide with a particle size of 50-100 nm;

[0014] And / or, the organic sodium source is at least one of sodium citrate, sodium gluconate, and sodium stearate.

[0015] Furthermore, the sintering temperature is 450-550℃ and the time is 5-10h.

[0016] Furthermore, the titanium dioxide and organic sodium source are mixed at a Na:Ti molar ratio of (2.1-2.3):3, with the sodium source providing a margin to prevent sodium volatilization during sintering. The thickness of the carbon layer in the Na2Ti3O7@C composite material is 2-5 nm.

[0017] Furthermore, in S1, the particle size of γ-Al2O3 in the γ-Al2O3 suspension is ≤20nm, the concentration of γ-Al2O3 is 5-10wt%, and the solvent is an organic solvent; it also includes a dispersant of 1-10% by mass of γ-Al2O3.

[0018] Furthermore, the organic solvent is selected from at least one of ethanol, isopropanol, and acetone, and the dispersant is selected from at least one of polyacrylic acid, polyethylene glycol, and polyvinylpyrrolidone.

[0019] Furthermore, in S1, the low-temperature sintering temperature is 200-300℃, the time is 2-3 hours, and the generated Al2O3 layer has a mesoporous structure with a pore size of 2-5 nm. The low-temperature sintering also preserves the inner elastic layer sp. 2The structure (Raman ID / IG = 0.85) avoids NTO phase transition caused by high temperature.

[0020] Furthermore, in S1, the concentration of the Na2Ti3O7@C composite material in the mixture is 5-10 wt%.

[0021] Furthermore, in S2, the hydrothermal treatment temperature is 70-90℃ and the time is 3-5h.

[0022] The second aspect of the present invention provides a sodium titanate anode material prepared by the preparation method described in the first aspect.

[0023] The third aspect of this invention provides the application of the sodium titanate anode material described in the second aspect in sodium-ion batteries or lithium-ion batteries.

[0024] The beneficial effects of this invention are:

[0025] In this invention, a C layer, an Al2O3 layer, and a NaAlO2 layer are sequentially coated on the surface of Na2Ti3O7 material. The outer NaAlO2 layer serves as a protective layer and also provides ion channels as an ion conductor. The middle mesoporous Al2O3 layer blocks electrode liquid corrosion, and the inner carbon layer increases the material's conductivity.

[0026] This invention uses a one-step coating method with an organic sodium source, avoiding complex processes such as template methods and sol-gel methods, to obtain a nanoscale carbon material coating layer, thus solving the problem of low loading in electrode preparation processes.

[0027] This invention utilizes sodium hydroxide (NaOH) hydrothermal treatment to generate an outer NaAlO2 layer on the surface of an Al2O3 layer in situ. The NaAlO2 and Al2O3 chemically bonded interface are seamlessly integrated, preventing electrode liquid penetration, suppressing side reactions, improving safety, and ensuring long-term cycling stability. The hydrothermal reaction is a one-step synthesis process, eliminating the need for sintering, avoiding damage to the substrate material, and reducing energy consumption while improving efficiency. Attached Figure Description

[0028] To more clearly illustrate the technical solution of the present invention, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0029] Figure 1 This is a 0.5C charge / discharge curve of the negative electrode material battery of Embodiment 1 of the present invention;

[0030] Figure 2 This is the capacity retention curve of the negative electrode material in Embodiment 1 of the present invention. Detailed Implementation

[0031] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] This embodiment provides a method for preparing a highly stable sodium titanate anode material, including the following steps:

[0033] S1. The Na2Ti3O7@C composite material was impregnated in γ-Al2O3 suspension to obtain a mixed solution. After stirring and centrifugation, it was sintered at low temperature to form an Al2O3 layer on the surface of the Na2Ti3O7@C composite material, thus obtaining the Na2Ti3O7@C-Al2O3 composite material.

[0034] S2. The Na2Ti3O7@C-Al2O3 composite material was immersed in NaOH solution, and hydrothermal treatment was performed to convert the surface layer of Al2O3 into NaAlO2, thus obtaining the highly stable sodium titanate anode material Na2Ti3O7@C-Al2O3 / NaAlO2.

[0035] This embodiment reduces the decomposition rate of the electrolyte through an Al2O3 / NaAlO2 bilayer coating. The mesoporous Al2O3 layer blocks electrode corrosion, while NaAlO2, containing sodium ions, acts as a protective layer and enhances the ionic conductivity of the negative electrode material. The NaAlO2 layer promotes the absorption of sodium ions. + Migration. The outer NaAlO2 layer is generated in situ by hydrothermal treatment with sodium hydroxide (NaOH) on the surface of Al2O3 layer. Compared with the process of directly physical / chemical coating of NaAlO2 on the surface of alumina, it has the following technical advantages: (1) The surface of Al2O3 is converted to an outer NaAlO2 layer by hydrothermal treatment with sodium hydroxide (NaOH). - Chemical bonding occurs, and a dense and uniform NaAlO2 layer (thickness controllable to the nanometer scale) is generated in situ. The NaAlO2 coating layer and the inner Al2O3 layer are seamlessly combined, avoiding interfacial corrosion caused by electrolyte penetration; (2) The generated NaAlO2 has a continuous crystal structure, its sodium ion diffusion channels are complete, the sodium ion transport path is unobstructed, and the electrode polarization is low; (3) Low temperature hydrothermal conditions (70-90℃) avoid thermal damage to the substrate material (such as carbon coating layer or sodium titanate core) caused by high temperature; at the same time, the process temperature is low, and the energy consumption is reduced by 40%-60%; the target product is generated in one step without subsequent sintering, and the process flow is shortened by about 30%.

[0036] As a preferred embodiment, the preparation method of the Na2Ti3O7@C composite material is as follows: titanium dioxide, an organic sodium source, and water are mixed and sintered under a protective atmosphere. The organic sodium source decomposes to generate a carbon layer that coats sodium titanate particles, forming the Na2Ti3O7@C composite material. This one-step coating method using the organic sodium source avoids complex processes such as template methods and sol-gel methods, obtaining a nanoscale carbon material coating layer and solving the problem of low loading in electrode preparation processes. Specifically, the titanium dioxide is anatase titanium dioxide with a particle size of 50-100 nm; the organic sodium source is at least one of sodium citrate, sodium gluconate, and sodium stearate; the sintering temperature is 450-550℃, and the time is 5-10 h; the protective atmosphere is argon or an argon / hydrogen mixture (volume ratio Ar / H2 = 95:5); the titanium dioxide and organic sodium source are mixed at a Na:Ti molar ratio of (2.1-2.3):3; and the thickness of the carbon layer in the Na2Ti3O7@C composite material is 2-5 nm.

[0037] In a preferred embodiment, in S1, the particle size of γ-Al2O3 in the γ-Al2O3 suspension is ≤20nm, the concentration of γ-Al2O3 is 5-10wt%, and the solvent is an organic solvent; it also includes a dispersant at 1-10% by mass of γ-Al2O3. The organic solvent is selected from at least one of ethanol, isopropanol, and acetone, and the dispersant is selected from at least one of polyacrylic acid, polyethylene glycol, and polyvinylpyrrolidone; the low-temperature sintering temperature is 200-300℃, and the time is 2-3h, resulting in an Al2O3 layer with a mesoporous structure and a pore size of 2-5nm, and the low-temperature sintering retains the inner elastic layer sp. 2 The structure (Raman ID / IG = 0.85) avoids NTO phase transformation caused by high temperature; the concentration of Na2Ti3O7@C composite material in the mixture is 5-10 wt%.

[0038] In a preferred embodiment, in S2, the hydrothermal treatment temperature is 70-90°C and the time is 3-5 hours.

[0039] Example 1

[0040] This embodiment relates to a method for preparing a highly stable sodium titanate anode material, including the following steps:

[0041] (1) Preparation of Na2Ti3O7@C composite material: Anatase TiO2 (particle size 80nm, purity ≥99.9%), sodium citrate and water were ball-milled and mixed (ball ratio 5:1, speed 300rpm, time 4h) by molar ratio Na:Ti=2.2:3. The mixture was then sintered at 500℃ for 6h under a protective atmosphere (volume ratio Ar / H2=95:5). The organic sodium source was decomposed to generate carbon layer coated sodium titanate particles, thus forming Na2Ti3O7@C composite material.

[0042] (2) Preparation of γ-Al2O3 suspension: γ-Al2O3 (particle size 20nm) was dispersed in ethanol (solid content 5wt%), and polyacrylic acid (PAA, MW=2000) was added as a dispersant (γ-Al2O3:PAA=10:1w / w). The mixture was ultrasonically treated for 30min to obtain γ-Al2O3 suspension.

[0043] (3) The Na2Ti3O7@C composite material obtained in step (1) is immersed in the γ-Al2O3 suspension obtained in step (2) to obtain a mixed solution, wherein the concentration of Na2Ti3O7@C composite material in the mixed solution is 10wt%. After stirring for 2h and centrifuging, the mixture is sintered at 300℃ for 2h to form an Al2O3 layer on the surface of the Na2Ti3O7@C composite material, thus obtaining the Na2Ti3O7@C-Al2O3 composite material.

[0044] (4) The Na2Ti3O7@C-Al2O3 composite material was immersed in 1M NaOH solution and hydrothermally treated at 80℃ for 4h to convert the surface layer of Al2O3 into NaAlO2, thus obtaining the highly stable sodium titanate anode material Na2Ti3O7@C-Al2O3 / NaAlO2.

[0045] Comparative Example 1

[0046] The difference between this comparative example and Example 1 is that step (4) is omitted, while other steps and parameters remain unchanged, to prepare the Na2Ti3O7@C-Al2O3 composite material.

[0047] Comparative Example 2

[0048] The difference between this comparative example and Example 1 is that steps (2)-(4) are omitted, while other steps and parameters remain unchanged, to prepare the Na2Ti3O7@C composite material.

[0049] Comparative Example 3

[0050] The difference between this comparative example and Example 1 is that step (4) does not use an in-situ hydrothermal reaction conversion method, but instead directly coats NaAlO2 onto the surface of the Na2Ti3O7@C-Al2O3 composite material, specifically:

[0051] (a) Pre-synthesized NaAlO2 powder:

[0052] Al(NO3)3·9H2O and NaOH were dissolved in deionized water at a molar ratio of 1:3, and the mixture was subjected to hydrothermal reaction at 80℃ for 12 hours. After centrifugation, drying, and grinding, NaAlO2 powder (average particle size 200nm) was obtained.

[0053] (b) Mechanically mixed coating:

[0054] The Na2Ti3O7@C-Al2O3 composite material prepared in step (3) of Example 1 was mixed with the NaAlO2 powder obtained in step (a) at a mass ratio of 95:5, ethanol was added (solid-liquid ratio 1:10), and the mixture was ball-milled for 6 hours (400 rpm) and vacuum dried at 60°C for 12 hours.

[0055] (c) High-temperature sintering:

[0056] The temperature was increased to 500℃ at 5℃ / min and held for 2 hours under an Ar atmosphere, so that the NaAlO2 particles partially melted and adhered to the surface of the composite material to form a physical coating layer.

[0057] Comparative Example 4

[0058] The difference between this comparative example and Example 1 is that in step (1), the organic sodium source sodium citrate is replaced with sodium carbonate, while the other steps and parameters remain unchanged.

[0059] Test case

[0060] Using the negative electrode materials obtained in Example 1 and Comparative Examples 1-4 as the negative electrode active material, acetylene black as the conductive agent, and PVDF as the binder, the active material, conductive agent, and binder were added to the solvent NMP at a mass ratio of 8:1:1 to obtain a slurry with a binder concentration of 5wt%. The slurry was manually coated onto the surface of 6μm aluminum foil and dried to obtain the electrode sheet. The electrode sheet was used as the working electrode, and the sodium sheet as the counter electrode. The electrolyte was 1mol / L NaPF6 (solvents were ethylene carbonate (EC) and dimethyl carbonate (DMC), with a volume ratio of 1:1). A half-cell was assembled for electrochemical testing. Figure 1 As shown, the negative electrode material battery obtained in Example 1 has an initial discharge capacity of 152 mAh / g at 0.5C, and a capacity retention rate of 97.3% after 400 cycles. (Reference) Figure 2 The electrochemical performance test results of the sodium-ion batteries using the negative electrode materials of Example 1 and Comparative Examples 1-4 are shown in Table 1.

[0061] Table 1

[0062]

[0063] Comparing Example 1 and Comparative Example 1, it can be seen that the absence of a NaAlO2 outer layer in Comparative Example 1 reduces the sodium ion transport rate, decreases the rate performance, and causes a weak reaction between the exposed NaAlO2 surface and the electrolyte (EC / DMC), resulting in a thicker SEI film and a reduced capacity retention. In Comparative Example 2, only a carbon layer is coated, resulting in good initial electrochemical performance, but due to the lack of NaAlO2 and Al2O3 coatings, Ti… 3+ Oxidized to Ti by electrolyte 4+In Comparative Example 3, NaAlO2 was directly coated onto the Al2O3 layer without in-situ hydrothermal reaction. The directly coated NaAlO2 was prone to local agglomeration or discontinuous coverage, and the coating layer had cracks or pores, which accelerated the reaction with the electrolyte and reduced the capacity retention. In Comparative Example 4, there was no organic carbon coating, so the specific capacity of the battery decreased. The discontinuous carbon layer could not effectively block the electrolyte penetration, and the interfacial side reactions were aggravated, resulting in a decrease in capacity retention.

[0064] In summary, this invention sequentially coats the surface of Na2Ti3O7 material with a C layer, an Al2O3 layer, and a NaAlO2 layer. The outer NaAlO2 layer serves as a protective layer and also provides ion channels as an ion conductor. The middle mesoporous Al2O3 layer blocks electrode liquid corrosion, and the inner carbon layer increases the material's conductivity. A one-step coating method using an organic sodium source avoids complex processes such as template methods and sol-gel methods, resulting in a nanoscale carbon material coating layer and solving the problem of low loading in electrode preparation. The outer NaAlO2 layer is generated in situ through hydrothermal treatment with sodium hydroxide (NaOH) on the Al2O3 layer surface. The seamless chemical bonding interface between NaAlO2 and Al2O3 prevents electrode liquid penetration, suppresses side reactions, improves safety, and ensures long-term cycling stability. The one-step hydrothermal synthesis eliminates the need for sintering, avoiding damage to the substrate material while reducing energy consumption and improving efficiency.

[0065] The present invention has been described in detail above with reference to specific embodiments and exemplary examples; however, these descriptions should not be construed as limiting the present invention. Those skilled in the art will understand that various equivalent substitutions, modifications, or improvements can be made to the technical solutions and embodiments of the present invention without departing from the spirit and scope of the invention, and all such modifications and improvements fall within the scope of the present invention. The scope of protection of the present invention is defined by the appended claims.

Claims

1. A method for preparing a highly stable sodium titanate anode material, characterized in that, Includes the following steps: S1. The Na2Ti3O7@C composite material was impregnated in γ-Al2O3 suspension to obtain a mixed solution. After stirring and centrifugation, it was sintered at low temperature to form an Al2O3 layer on the surface of the Na2Ti3O7@C composite material, thus obtaining the Na2Ti3O7@C-Al2O3 composite material. S2. The Na2Ti3O7@C-Al2O3 composite material was immersed in NaOH solution, and hydrothermal treatment was performed to convert the surface layer of Al2O3 into NaAlO2, thus obtaining the highly stable sodium titanate anode material Na2Ti3O7@C-Al2O3 / NaAlO2. The preparation method of the Na2Ti3O7@C composite material is as follows: titanium dioxide, organic sodium source and water are mixed and sintered under a protective atmosphere. The organic sodium source is decomposed to generate a carbon layer that coats sodium titanate particles, thus forming the Na2Ti3O7@C composite material.

2. The method for preparing the highly stable sodium titanate anode material as described in claim 1, characterized in that, The titanium dioxide is anatase titanium dioxide with a particle size of 50-100 nm. And / or, the organic sodium source is at least one of sodium citrate, sodium gluconate, and sodium stearate.

3. The method for preparing the highly stable sodium titanate anode material as described in claim 1, characterized in that, The sintering temperature is 450-550℃ and the time is 5-10h.

4. The method for preparing the highly stable sodium titanate anode material as described in claim 1, characterized in that, In S1, the particle size of γ-Al2O3 in the γ-Al2O3 suspension is ≤20nm, the concentration of γ-Al2O3 is 5-10wt%, and the solvent is an organic solvent; it also includes a dispersant of 1-10% by mass of γ-Al2O3.

5. The method for preparing the highly stable sodium titanate anode material as described in claim 1, characterized in that, In S1, the low-temperature sintering temperature is 200-300℃ and the time is 2-3h.

6. The method for preparing the highly stable sodium titanate anode material as described in claim 1, characterized in that, In S1, the concentration of the Na2Ti3O7@C composite material in the mixture is 5-10 wt%.

7. The method for preparing the highly stable sodium titanate anode material as described in claim 1, characterized in that, In S2, the hydrothermal treatment temperature is 70-90℃ and the time is 3-5h.

8. A sodium titanate anode material prepared by the preparation method according to any one of claims 1-7.

9. The application of the sodium titanate anode material according to claim 8 in a sodium-ion battery or a lithium-ion battery.

Citation Information

Patent Citations

  • Nanometer flaky carbon-coated sodium titanate composite material and preparation method and application thereof

    CN118529769A

  • A preparation method of a spherical carbon-coated titanate composite negative electrode material

    CN109244415A

  • Sodium metaaluminate-coated core-shell type hard carbon composite material as well as preparation method and application thereof

    CN116864655A

  • Alumina-coated silica composite material and preparation method thereof

    CN118791028A